Rwandan teacher training college’s mathematics teachers’ pedagogical content knowledge for teaching: assessment toward competency-based curriculum - Habiyaremye, Hashituky Telesphore; Ntivuguruzwa, Celestin; Ntawiha, Philothere (Frontiers in Education, 2023)
Introduction Teachers’ knowledge and positive attitudes significantly impact educational settings. This study aimed to assess teachers’ mathematical knowledge for teaching (MKT) and their pedagogical content knowledge (PCK) attitudes. Methodology It was conducted on all 23 mathematics teachers from Rwandan teacher training colleges (TTCs). Employing a survey design, standardized performance and attitude tests were utilized, employing instruments known for their standardization, validity, and reliability. Results The findings informed that teachers possess a low MKT but a high PCK attitude. Thus, they performed the MKT test poorly as the average score was below 50%. However, teachers were found to have better content knowledge than other MKT constructs and performed better in pattern function and algebra than in other areas of mathematics. Teachers demonstrated a highly positive attitude toward integrating PCK in teaching mathematics. Discussion Such a positive attitude was inferred from the pedagogical training offered by implementing a competency-based curriculum. Therefore, teachers need to improve their MKT performance, and more research is needed on other teachers apart from those in TTCs.